Myth and philosophy from the Presocratics to Plato - Morgan, Kathryn A. (Cambridge University Press, 2000)
This book explores the complex relationship between myth and philosophy in writings by Greek intellectuals between the late sixth and mid fourth centuries BC. It shows how Plato and other philosophers used myth to express philosophic problems and traces a tradition of strictly rational and philosophical myth through two centuries.